Model Peningkatan Minat Petani pada Penerapan Teknologi Tanam Jajar Legowo Padi Sawah di Kecamatan Cikoneng Ciamis - Lukman Effendy; Carla Yunika (AGRITEXTS: Journal of Agricultural Extension, 2020)
Jajar Legowo planting system (Jarwo) has become a program to boost rice production in the last     two decades. Through various means of socialization have been carried out and many farmers’ fields become demonstration plots. However, this innovation has not been “down to earth” and has not yet become a patanic need, so research is needed to increase the interest of farmers in Cikoneng Ciamis District, which aims to: (1) describe the level of interest of farmers in the application of the jarwo system, (2) identify the factors that influence the interests of farmers , and (3) designing a model to increase farmers’ interest. The study was conducted from April to June 2019 on 85 respondents from a population of 235 farmers using the Slovin formula. Data collected through direct interviews using a questionnaire that has been tested for reliability. After being analyzed with descriptive statistics and multiple linear regression analysis, the results are obtained: (1) most respondents (72.94%) have a sufficient level of interest in the application of jarwo, (2) the characteristics of farmers (X1) and external factors (X2) influence real (p≤0.05) to the interests of farmers, and (3) strategies to increase farmers’ interest in applying jarwo can be done by paying attention; farmers who are in the productive age group (45-55 years), have a minimum of primary school education, have experience in farming for a minimum of 7-9 years, and have enough land around 2,000 - 4,000 square meters.